Novice teachers’ beliefs and fears on bullying in schools in South Africa - Mahabeer, Pryah (2020)
Worldwide, and in developing countries like South Africa, bullying and violence in schools are a prevalent problem. Negotiating and managing bullying in schools has become progressively challenging for teachers, more so for novice teachers entering the profession. Through semi-structured interviews, this interpretivist qualitative study explores the fears and beliefs of four novice teachers within the KwaZulu-Natal province in South Africa. Using narrative analysis, novice teachers attributed their understanding, worldviews, beliefs, fears and the manner in which they responded to bullying instances to: their biographical backgrounds, their personal beliefs and attitudes, social and contextual factors. They demonstrated an understanding of bullying, and recognised the prevalence and persisting problem of bullying in schools. They recalled from their growing up years how they experienced bullying, directly or indirectly, consciously or unconsciously, from their own personal histories, attitudes and beliefs. They expressed fears about not effectively identifying and responding to bullying behaviours. Lastly, teachers associated bullying with an imbalance of power. Although teachers were aware of informal anti-bullying interventions, they stressed the lack of concrete formal intervention strategies to reduce and stop bullying. The teachers recommended a collaborative and democratic process of all stakeholders deciding policies and crafting customised practical intervention strategies, rather than a generic approach to eliminating bullying and violence in schools.Keywords: anti-bullying, beliefs, bullying, fears, school violence, teachers
Keywords: anti-bullying; Beliefs; Bullying; Fears; School violence; Teachers